PERLINDUNGAN HUKUM TERHADAP HAK ULAYAT MASYARAKAT HUKUM ADAT BATIN HITAM SUNGAI MEDANG DESA KESUMA KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN, PROVINSI RIAU (STUDI PUTUSAN NOMOR 113/PID.B/2019/PN PLW) - Yunita Baransano; Hanafi Tanawijaya (Jurnal Hukum Adigama, 2020)
The problem that will be discussed in this research is how the agreement for the management of the customary land of Batin Hitam Sungai Medang customary community, Kesuma Village, Pangkalan Kuras District, Pelalawan Regency, Riau Province with PT. Arara Abadi and how its legal protection for holders of customary rights over their ulayat lands, efforts to implement various laws and regulations on customary law communities and their customary rights as an effort to implement the boundary agreement for PT. Arara Abadi. This type of research is normative, so the data sources used are primary data from interviews, secondary data from libraries and tertiary data from dictionaries, media, and encyclopedias. Interview data collection techniques, and literature review. Legal protection is an effort to protect the ulayat rights of the Batin Hitam customary law community in the former IUPHHK-HTI area of PT. Arara Abadi, due to the dispute settlement with the Batin Hitam customary community with the agreement that: a) The 1.5 km area on the left and right of the Medang river or approximately 4,300 ha, was excluded from PT. Arara Abadi to enclave and preserve. b) Whereas the 54 hectare area deemed to have been damaged by the Batin Hitam customary law community includes the area of customary land. field.